EDUKASI AGAMA DI ERA DIGITAL: ANALISA PODCAST LOGIN SEBAGAI PEMANFAATAN PLATFORM YOUTUBE UNTUK PENYEBARAN DAKWAH DAN PEMBELAJARAN KEAGAMAAN - Hidayatulloh, Ragil; Anggoro Adit Haptono; Taufiq Tri Winardi; Wahyu Pratama Andhika Maheswara; Muhammad Alvian Jaya; Erwin Kusumastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Freedom of religious preaching in Indonesia, although guaranteed constitutionally, often triggers disputes amidst diversity of beliefs. Da'wah activities based on the enlightenment of the people, of course, must require a comprehensive understanding of religious tolerance. Tolerance, which etymologically means patience, open-mindedness or showing patience, must be reflected in the implementation of da'wah activities. Religious tolerance is very important when viewed from the condition of nations and countries with multi-ethnic, cultural and religious social life. In the context of the developing digital era, YouTube has modernized methods of religious preaching and learning, providing a broad platform for the dissemination of religious teachings. Analysis of religious content on YouTube reveals the importance of the integrity of the host, the relevance of the material, and the interactivity of the platform in educating and increasing tolerance and understanding between religious believers. Although YouTube facilitates widespread access to religious information, challenges regarding the credibility and veracity of information demand strong digital literacy from users. Face-to-face learning methods are still needed in Islam as a foundation for understanding religion, emphasizing the importance of direct interaction in religious education. This study highlights the need for innovative approaches in creating da'wah content on YouTube to attract young people in particular, strengthen their religious awareness, and synchronize da'wah and religious education with the needs of today's digital generation.